Green Supply Chain Management for Carbon Accountability - Liew, Millie; Cao, June (Elsevier, 2024)
As disclosure mandates shift their focus towards supply chain carbon accountability, firms are compelled to enhance carbon outcomes throughout their supply chain. The literature suggests that green supply chain management (hereafter, GSCM) plays an essential role in enhancing firms' environmental performance. However, there is a dearth of evidence on the possible informational effects of GSCM on Scope 3 carbon outcomes despite their mutual linkage to supply chains. Using two novel measures of GSCM quality, defined as the extent to which environmental objectives are integrated into supply chain management processes, we find that higher GSCM quality increases the likelihood of a focal customer's Scope 3 carbon disclosures and reduces its Scope 3 carbon footprint. These effects of GSCM quality are realized through improvements in relational trust among customer-supplier relationships and in suppliers' environmental innovation capabilities. Further analysis reveals that the effects of GSCM quality are realized among durable customer-supplier relationships. We identify GSCM quality as an essential and distinct component of corporate environmental governance. These findings highlight the importance of GSCM quality for attaining supply chain carbon transparency and accountability.